Comportamento das curvas de saturação da água e LNAPL em solo da formação Rio Claro - Santos, Eduardo Patrício dos [UNESP] (2014)
Experiments for obtaining saturation curves for the water-air systems and Air-Kerosene were performed in tropical soil samples collected in typical outcrop of the Rio Claro Formation. The determination of saturation curves through direct experiments was conducted in the Laboratory of Remediation Areas Impacted by Oil (RAIH), UNESP, Rio Claro and were obtained using the porous plate funnel method and the Richards chambers method, the latter was only applied to the Air-Water System. In these experiments it was established criteria and new improvements in the analytical procedures described in literature, particularly on the determination of the saturation curve for the Air-Kerosene system. The results obtained in the laboratory were plotted into graphs relating the applied pressure to the volumetric saturation of the porous medium and were adjusted to the unimodal model (van Genuchten) and bimodal model (Durner). The best fit obtained for each sample indicated bimodal behavior for the distribution of pore size of the studied soil. Theoretical models proposed by Lenhard and Parker (1987) and Charbeneau (API, 2007) were also used to indirectly estimate the saturation curves of the Air-Kerosene system from the experimental data obtained for the Air- Water system. These models were originally developed for the calculation of the estimate of the recovery LNAPL porous in remediation processes. They indicate that the models show differences in the results of the saturation curves when compared between themselves and also for the data obtained experimentally for the air kerosene system. Since the amount of recoverable LNAPL can be estimated by the area underneath the saturation curve and considering that the experimental data are differ from the data obtained indirectly, we concluded that these indirect theoretical models may not correspond to the actual curves, providing unrealistic estimates of time and costs for the remediation